2023
DOI: 10.1021/acssuschemeng.3c04957
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Base-Catalyzed Valorization of Food Waste into Lactic Acid at Mild Conditions with the Pretreatment Using HCl Recovered from PVC

Renjie Yang,
Pengfei Chen,
Heng Zhong
et al.

Abstract: Lactic acid (LA) serves as a crucial platform chemical and monomer for the production of biodegradable plastic known as polylactic acid. Presently, LA is predominantly derived from the fermentation of crop syrups, a process that consumes substantial grain reserves and poses a significant threat to food security. Food waste (FW) represents a promising alternative source for LA production due to its abundant carbohydrate content. This study proposes an efficient and expeditious method for converting FW into LA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Compared with the chemocatalysis of lactic acid production from food waste, it was found that both biochemical conversion and chemocatalysis demonstrated appealing and comparable results. 48 As there is no one good solution that fits all, it is beneficial to explore diverse technological approaches to address the pressing issue of food waste. To further enhance lactic acid production, future work should target improved metabolic performance through the regulation of metabolic pathways to minimise the formation of byproducts.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the chemocatalysis of lactic acid production from food waste, it was found that both biochemical conversion and chemocatalysis demonstrated appealing and comparable results. 48 As there is no one good solution that fits all, it is beneficial to explore diverse technological approaches to address the pressing issue of food waste. To further enhance lactic acid production, future work should target improved metabolic performance through the regulation of metabolic pathways to minimise the formation of byproducts.…”
Section: Resultsmentioning
confidence: 99%